DEFINITIONS OF FINANCIAL SERVICE: SEMANTIC ANALYSIS OF THE GENERAL CONCEPT - Yatsenko, Ivan (Socio-economic relations in the digital society, 2020)
In the article the results of the semantic analysis of the definitions of financial services presented in the modern economic literature are summarized. The semantic core of the concept of «financial service» has been formed. The set of definitions of financial services, illuminating its essence from different angles, systematized around the semantic core. They are: activities to manage cash flows in the process of financial transactions; the result of interactions between financial institutions producing financial services and their customers; a set of transactions with financial assets in the interests of the client, mainly at his expense; a product that has consumer and exchange value, the demand for which is determined by the needs of market participants regarding the satisfaction of their financial interests; relations for the transformation of funds into money capital; financial liabilities arising from a financial service provider to its consumers in connection with the movement of money capital; component of a financial product, which is a form of presentation of a financial service on the market; a financial procedure that provides for the implementation of a list of actions with financial assets in a certain sequence. Based on the results of semantic analysis, the author’s definition of the essence of the concept of financial services is formulated. A financial service is defined as a set of financial technologies used by financial corporations in cash flow management processes, which are mediated by the movement of financial assets, counter financial liabilities and are implemented through appropriate financial instruments in order to realize the financial interests of economic agents. Unlike other definitions, in the author’s definition the institutional structure of the financial sector is taken into account and the importance of financial technologies in the provision of financial services is emphasized.